Fracture stratigraphy and mechanical stratigraphy in sandstone: A multiscale quantitative analysis. (November 2022) - Liu, Jingshou; Chen, Peng; Xu, Ke; Yang, Haimeng; Liu, Hejuan; Liu, Yang
Abstract: Mechanical stratigraphy can provide valuable knowledge for evaluating and predicting the distribution of structural fractures and in situ stress. The fracture stratigraphy and mechanical stratigraphy of the Triassic Yanchang Formation sandstone reservoirs in the Huaqing area of the Ordos Basin were investigated. In this study, borehole images were used to identify and characterize the orientation and properties of natural fractures, and array acoustic logs were used to analyze the rock mechanical properties. By considering the positional and scale cycles, the mechanical stratigraphy and areal fracture density at multiple scales were calculated, and the statistical correlation between them was analyzed. The results show that when the dynamic Young's modulus is less than 45 GPa, the areal fracture density generally increases with increasing Young's modulus; when the dynamic Young's modulus is greater than 48.5 GPa, the areal fracture density decreases with increasing dynamic Young's modulus. Additionally, the areal fracture density peaks when the dynamic Young's modulus is in the range of 45–48.5 GPa. In general, the dynamic Poisson's ratio is negatively correlated with the areal fracture density at multiple scales; when the dynamic Poisson's ratio is less than 0.24, the areal fracture density rapidly decreases as the dynamic Poisson's ratio increases; when the dynamic Poisson's ratio is greater than 0.24, the dynamic Poisson's ratio is only weakly correlated with the areal fracture density. The fitting results between the mechanical stratigraphy and areal fracture density show that the mathematical model relating these two parameters is related to the statistical scale. Highlights: A multiscale quantitative analysis of the fracture and mechanical stratigraphy is performed. As Young's modulus increases, the fracture density first increases and then decreases. With the increase in Poisson's ratio, the fracture density decreases, and the correlation between the two weakens.